(3Yjhf CNHGQ GdQVGs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3eMeO bGSe Hf ceGd GdOjf GdTjQGRjs)
(3ChdgG (B:s
(3Ydjg hbY Edi bUjOJGf ef bUGFO GdUGMH GdLdjd cGaj GdcaGI CHj GdbGSe ESeGYjd Hf YHGO(B...s
(3BNQgG (B:s
(3hdeG NQL CHh GdMSjf eMeO Hf CMeO Hf RjGO GdYdhj QMeg Gddg hHGjY dg YTQhf Cda QLd HfjSGHhQ(B... (3hbO BdjJ Ydi faSj Cf dG CaGQb gPG GdeTgO eG HbjJ(B. (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B274s
(3GdPQjYI, HQbe(B: 2367s
(3GdPQjYI, HQbe(B: 2367s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B133s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs